1986
DOI: 10.1111/j.1467-9906.1986.tb00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Satisfaction, Expectations, and Urban Revitalization

Abstract: This study examines the role of residential satisfaction and expectations as determinants of neighhorhood revitalization in a working class neighborhood. An extensive set of hackground and social-psychological factors are identifed, and their effects on housing renovation and the wish to move are assessed. The findings suggest that renovation is a more complex activity than often portrayed with neither the objective characteristics of the neighborhood or the residents adequate as explanations f o r explaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The connection between gentrification and residential satisfaction has not been studied in depth as pointed out by Freeman (2004) and Nachmias and Palen (1986). Sullivan (2006, 2007) conducted a survey in Portland, Oregon asking residents if they thought their neighbourhood was getting better or worse, but did not examine their views as to the changing attributes.…”
Section: The Literaturementioning
confidence: 99%
“…The connection between gentrification and residential satisfaction has not been studied in depth as pointed out by Freeman (2004) and Nachmias and Palen (1986). Sullivan (2006, 2007) conducted a survey in Portland, Oregon asking residents if they thought their neighbourhood was getting better or worse, but did not examine their views as to the changing attributes.…”
Section: The Literaturementioning
confidence: 99%
“…To sum up, although earlier studies found several estimating factors to identify the current level of resident satisfaction, relatively little attention has hitherto been paid to understanding the resident's future expectations in urban renewal projects. According to the study of Nachmias and Palen (1986), the expected neighbourhood improvement is a more meaningful factor than the level of current neighbourhood satisfaction. This factor has positive influences on residents' plans to move and renovating their own houses.…”
Section: Determinants Of Resident Satisfactionmentioning
confidence: 99%